2019
DOI: 10.1177/1049909119897260
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Patterns Before and After an Inpatient Palliative Care Consultation

Abstract: Background: To the best of our knowledge, the change in opioid prescription patterns upon referral to a palliative care team (PCT) was not previously investigated in the Middle East. Objective: This study aimed to explore the change in the pattern of opioid prescription and the pain scores before and after referring inpatients to a PCT. Methods: We conducted a retrospective review of patients’ records including all inpatients ≥15 years newly referred to the PCT over a period of 21 months at King Faisal Special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Severe sepsis is the leading cause of death in ICUs [ 21 ]. Opioids are the primary treatment for pain related to advanced and progressive diseases, especially when withdrawing life-sustaining measures [ 22 ]. Furosemide and albumin are used to treat fluid retention [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe sepsis is the leading cause of death in ICUs [ 21 ]. Opioids are the primary treatment for pain related to advanced and progressive diseases, especially when withdrawing life-sustaining measures [ 22 ]. Furosemide and albumin are used to treat fluid retention [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe sepsis is a leading cause of death in ICUs [21]. Meanwhile, opioids are the primary treatment for pain related to advanced and progressive diseases, especially when withdrawing life-sustaining measures [22]. Furosemide and albumin are used to treat uid retention [23].…”
Section: Discussionmentioning
confidence: 99%
“…27 Sadler et al also reported underutilization of PC services, with only 22 of 103 patients coming through the emergency room having had any PC involvement in the year preceding death. 27 Despite this underutilization of PC, several studies documented the benefits of this service, including shorter length of hospital stay, 12,29 superior opioid pain management, 30 slightly longer survival time, 28 and avoidance of unnecessary and aggressive treatment. 12,27 Notwithstanding the benefits of PC services, 1 study showed most patients (85.7%) still die in the hospital 11 due the lack of available home-based PC options.…”
Section: Utilization and Outcomes Of Specialty Carementioning
confidence: 99%